If `f(x)=f(-x)` for all `|x|ltR, f(x)-f(-x)` is a constant 0 function for all `|x|ltR.`

The constant 0 function has a **unique** power series that is ` `

` `

Therefore all the coefficients of the power series of f(x)-f(-x) ` ` are 0.

Now let's find the coefficients of f(x)-f(-x) as an expression of a_n

`f(x)-f(-x)=sum_0^(oo)a_nx^n-sum_0^(oo)a_n(-x)^n`

`f(x)-f(-x)=sum_0^(oo)(a_n-(-1)^na_n)x^n`

Hence` (a_n-(-1)^na_n)=0` for all n.

If n even `(-1)^n=1 ` and the condition becomes `a_n-a_n=0 ` which is true for any even n.

if n odd,` (-1)^n=-1` and the condition becomes `a_n+a_n=0. ` Therefore `a_n=0.`

**In conclusion if** `f(x)=f(-x)` , `a_n=0` **for all odd n**.

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now